Performance enhancement of PEM fuel cells using novel porous flow field designs - Sevinc, Huseyin; Hazar, Hanbey (Pergamon-Elsevier Science Ltd, 2026)
This study aims to enhance the performance and efficiency of proton exchange membrane fuel cells (PEMFCs) by employing novel bipolar plate designs that integrate porous flow field structures. Five distinct models (P1-P5) featuring open-cell porous domains were developed and compared against a conventional triple-serpentine configuration using three-dimensional CFD simulations. The objective was to assess the effects of porous domain geometry on current density, pressure drop, reactant distribution, and net power output. The results revealed that all porous flow field models exhibited improved electrochemical behavior, especially in the ohmic and mass transport loss regions. Among them, the P1 model achieved the highest current density (1.45 A/cm2) and power density (0.58 W/cm2) at 0.4 V, outperforming the benchmark by 21.6% and 21.5%, respectively. Despite increased pressure drops due to internal flow resistance in porous domains, net power output improved across all models, with P1 providing a 17.6% increase compared to the serpentine design. Species distribution analysis showed more uniform hydrogen and oxygen transport in porous configurations, resulting in better mass utilization. Experimental validation confirmed strong agreement between simulation and test data for both the P1 and reference designs. The study concludes that properly configured porous flow fields can significantly enhance PEMFC performance by improving mass transfer, current generation, and thermal distribution. However, careful tuning of the porous region's size, location, and number is essential to balance pressure losses and energy gains. These findings offer valuable insights for the next generation of high-performance and manufacturable PEMFC designs.
Keywords: Fuel cell; Porous flow field; Flow field design; Bipolar plate design; Cell performance